PEMBERDAYAAN MASYARAKAT DESA MELALUI SISTEM BUDIDAYA BIOFLOK UNTUK MENDUKUNG EKONOMI RUMAH TANGGA DAN KETAHANAN PANGAN MASYARAKAT BEBAS STUNTING - Mujiburrahmad, Mujiburrahmad; Satrio, Purwana; Manyamsari, Ira (Universitas Syiah Kuala, 2023)
Observation results show that this village is one of the river watersheds (DAS) whose springs come from the mountains, so it has the potential to be used as a freshwater fish cultivation area. Currently, the residents of Seni Antara Village generally use fish as their daily diet and obtain fish by purchasing it directly from the market and/or validating it through mobile fish sellers at competitive prices (relatively expensive) and a small portion of them search for it. own fish in the river. On the other hand, the village has the potential for land and air to be used by villagers to cultivate fish, but in reality only a few villagers do it and even then the management is not optimal. Based on the results of observations in the field and the results of the analysis of the problem situation in the field, several problem partners were found, namely: 1). Lack of community knowledge and skills regarding the biofloc cultivation system, 2). Lack of knowledge regarding processed products from fish raw materials, 3). Lack of public knowledge regarding the importance of preventing stunting by consuming healthy fish. Referring to the analysis of the results of the situation and the potential of partners and strengthened by the knowledge and experience of our team, we offer solutions that are easy, cheap and can be implemented sustainably. Implementation activities will begin with the coordination and outreach stage with partners for implementing activities, then continue with the provision of biofloc ponds and user training. This was followed by training on diversification of food products from fish, and counseling on stunting prevention. The target and output of this program is to increase partner income from woodfish production by IDR. 1,500,000 Rp. 5,000,000. Other publication output in accredited national journals and online national mass media. The results of the service implementation of this Real Work Lecture Assignment Service are (1) Increased knowledge, skills and abilities of partners in terms of implementing the biofloc cultivation system, (2) Increased knowledge, skills and abilities of partners in terms of implementing methods of food diversification from fish raw materials, ( 3) Increased knowledge, skills and abilities of partners regarding understanding stunting, how to prevent it and understanding the importance of consuming healthy fish, and (4) Increased knowledge, skills and abilities in running a business with good planning and partners also understanding business management, and ways to develop it.